2000
DOI: 10.1364/josaa.17.000001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the point-spread function for imaging in scattering media by use of polarization-difference imaging

Abstract: Polarization-difference (PD) imaging techniques have been demonstrated to improve the detectability of target features that are embedded in scattering media. The improved detectability occurs for both passive imaging in moderately scattering media (Ͻ5 optical depths) and active imaging in more highly scattering media. These improvements are relative to what is possible with equivalent polarization-blind, polarization-sum (PS) imaging under the same conditions. In this investigation, the point-spread functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The quasi-straightforward propagating photons pass the shortest path and are the least depolarized. This feature underlies polarization-difference imaging of objects hidden inside turbid media (see, e.g., [13][14][15][16]19,[23][24][25]). In this technique the imagebearing component of light is extracted by subtracting the detected cross-polarized signal from the co-polarized one.…”
Section: Polarization-difference Imaging Through Highly Scattering Mediamentioning
confidence: 98%
See 3 more Smart Citations
“…The quasi-straightforward propagating photons pass the shortest path and are the least depolarized. This feature underlies polarization-difference imaging of objects hidden inside turbid media (see, e.g., [13][14][15][16]19,[23][24][25]). In this technique the imagebearing component of light is extracted by subtracting the detected cross-polarized signal from the co-polarized one.…”
Section: Polarization-difference Imaging Through Highly Scattering Mediamentioning
confidence: 98%
“…In many experiments, detection of the polarization difference is employed (see, e.g., [13][14][15][16]19,[21][22][23][24][25]). This method is based on subtracting of the intensity of the cross-polarized component from the intensity of radiation with the initial polarization.…”
Section: Time-resolved Polarization Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyo simulated light transmitting procedures with single scatter theory and the Monte Carlo method [19]. The results showed that the point spread function (PSF) of the water was dependent on the polarization in the passive and active imaging, and the polarization-difference (PD) algorithm had a narrower PSF than polarization-sum (PS) algorithm.…”
Section: Introductionmentioning
confidence: 99%